2012
DOI: 10.1111/bjh.12097
|View full text |Cite
|
Sign up to set email alerts
|

Rapid T‐cell chimerism switch and memory T‐cell expansion are associated with pre‐engraftment immune reaction early after cord blood transplantation

Abstract: Rapid T-cell chimerism switch and memory T-cell expansion are associated with pre-engraftment immune reaction early after cord blood transplantation Cord blood (CB) contains immature immune cells and is thought to be less active in inducing allogeneic immune reaction than other sources of stem cells. However, a high incidence of immune-mediated complications has been reported, such as pre-engraftment immune reaction (PIR) and haemophagocytic syndrome (HPS) early after cord blood transplantation (CBT) (Kishi et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Previous reports have indicated that donor lymphocyte reconstitution is identified approximately 2 weeks after HSCT [26,27]. In the present study, lymphocyte recovery in the low ALC group was delayed starting at day 10, although it normalized at 3 months after HSCT.…”
Section: Discussionsupporting
confidence: 47%
“…Previous reports have indicated that donor lymphocyte reconstitution is identified approximately 2 weeks after HSCT [26,27]. In the present study, lymphocyte recovery in the low ALC group was delayed starting at day 10, although it normalized at 3 months after HSCT.…”
Section: Discussionsupporting
confidence: 47%
“…Among factors that could influence outcomes after dUCB allotransplant in adults, chimerism has been poorly investigated, thus far. Indeed, if a favorable impact of full donor chimerism on hematopoietic recovery or pre-engraftment syndrome has been already reported, no data regarding influence of mixed versus full TCC chimerism on long-term outcomes are yet available after dUCB RIC transplantations in adults [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategies to treat post-HSCT relapse historically consisted of withdrawal of immunosuppression or donor lymphocyte infusions, though several studies have shown efficacy in treating relapsed CML or Ph þ ALL with TKIs [8][9][10][11][12][13][14][15]. An increasing number of studies have also evaluated the prophylactic use of TKIs after transplantation in high-risk patients, including those with detectable BCR-ABL at the time of transplantation, though there are very limited data to guide their selection and administration [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Serum values for inflammatory cytokines such as IL-6 or IL-5, are elevated around the time of PIR onset [46,47]. We previously showed that rapid T cell chimerism switches to the donor type, and phenotypic conversion from naïve to memory T cells are significantly associated with the development of PIR [48]. Gutman et al also reported that CD8 + T cells predominately expressed effector memory or effector phenotype and produced IFN-γ in response only to non-engrafted units early after double-unit CBT, reflecting a specific immune response of the dominant, against the non-engrafted units [49].…”
Section: Early Immune Reactions After Cbt and Gvhd Prophylaxismentioning
confidence: 99%